‘How to Keep a Husband on Packaged Foods’ and Other Lessons: Gendered Education in the Canadian National Exhibition’s Women’s Division during the Kate Aitken Era, 1920s-1950s - Zankowicz, Kate (Cuizine, 2015)
Kate Aitken (1891-1971), perhaps best known as a broadcasting pioneer in Canadian history, was the first director of “Women’s Activities” at the Women’s Division of the Canadian National Exhibition (CNE) in Toronto. It was a position she officially took on in 1938 until her retirement in 1952. Aitken’s kitchen demonstration development, and her overwhelming success as an educator at the CNE offers a lens through which to examine the gendered education of food preparation, at a time when what constituted as ‘women’s work’ was itself being re-worked.This paper will investigate women’s programming at the CNE, and how it helped to support and construct women’s accepted roles as part of a wider discourse about women’s place both within and outside the home. Food played an intensely important part in this process. While the pedagogical purpose of many of the activities at the Women’s Building were described as the “capture, care and feeding of husbands,” Aitken’s use of food programming fulfilled multiple functions: as a tool for community organizing in her massive ‘ladies luncheons’ and her work with Women’s Institutes; as a gendered pedagogy in her restaurants, table-setting and cooking demonstrations and competitions; and as a means of teaching children and young people the skill of feeding themselves. As a woman whose work sat at the intersection of the ‘modern’ and the ‘traditional’ kitchen she also communicated important messages about shifting gender roles in the early to mid-twentieth century in Canada.